Javanese Politeness Experience as Depicted in Its Speech Levels of the Transactional Communication - Didik Rinan Sumekto; Imam Ghozali; Suhud Eko Yuwono; Gunawan Budi Santoso; Tukiyo Tukiyo (Humaniora, 2022)
Javanese interactions are bound by politeness speech levels. Ngoko, the lowest form, reflects the interactions between close equals, or persons of higher status towards those of lower status, whereas krama, the highest form, is used to address elders or those of higher status. This study aimed to disclose communication politeness as expressed by Javanese users in the public place. Twelve participants were enlisted, among them seven males and five females. Data were recorded from a smartphone and transcribed orthographically to obtain natural data, while data analysis used the interpretative approach, aiming to identify and code the transcripts. The results showed that five females consistently communicated with the krama speech level when dealing with other parties, whilst one female conveyed her ngoko speech level. On the other hand, one participant out of seven accordingly engaged in the krama speech level, whilst the other six participants consistently employed ngoko. These politeness patterns advocated both the interlocutor and hearer’s genuine interests and behavioral reflections within adaptable consequences, and expressed a sense of intimacy, respectfulness, functionality, and equality using various words, expressions, and meaningful talks that made up the existence of their social status. Females complimented others’ appearances, whereas males focused on predominance to show a sense of familiarity. This study concludes that Javanese politeness levels naturally constitute users’ daily speech habits that govern Javanese diglossia through their contextual adoption, adaptation, and reinterpretation. <w:LsdException Locked="false"